Training and Supervising Lay Providers in Kenya: Strategies and Mixed-Methods Outcomes☆☆☆. Issue 3 (August 2022) - Venturo-Conerly, Katherine; Roe, Elizabeth; Wasil, Akash; Osborn, Tom; Ndetei, David; Musyimi, Christine; Mutiso, Victoria; Wasanga, Christine; Weisz, John R.
Highlights: We detail lay provider training and supervision for an intervention for Kenyan youth. We found that a 10-hour lay clinician training led by undergraduates was effective. Lay providers reported experiencing personal growth because of their work. Lay providers emphasized the importance of supervision for collecting feedback. Findings can inform future training and supervision procedures for lay providers. Abstract: Objective: Training lay providers to deliver mental health interventions is both effective and cost-effective. However, more research is needed to document training and supervision procedures and to collect lay providers' feedback. Methods: This study documents training and supervision from a randomized controlled trial of the Shamiri intervention, a four-session, school-based intervention that significantly reduced symptoms of anxiety and depression in Kenyan adolescents. We delivered a 10-hour training to 13 lay providers, M ( SD )age = 21.00 (1.95), %female = 61.54. We also hosted 30-minute supervision meetings twice weekly. Training and supervision were delivered primarily by undergraduates. Independent raters coded session recordings for fidelity and quality of services, and we collected quantitative and qualitative feedback from lay providers. Results: Reliability and mean ratings for all six of our fidelity and quality measures (delivering required content, adhering to specified details, thoroughness, skillfulness, clarity, and purity) were very good to excellent. Lay provider quantitative ratings of training were also overwhelmingly positive, with an overall satisfaction rating of 6.46/7.00. We identified central qualitative themes in lay provider comments: Generally, comments about training style, content, and personal interactions were overwhelmingly positive, and many lay providers reported personal growth. Comments about timing and location of training were mixed. Conclusions: This study provides preliminary evidence that a very brief training delivered primarily by undergraduates can teach high school-graduate lay providers to deliver effective mental health interventions. Additionally, we discuss lessons learned and implications for future research, including the importance of considering local context when planning and of continuously collecting and addressing lay provider feedback.